Enhancing Indonesian Language Teachers’ Competence in Developing Differentiated Learning Materials for Speaking Skills - Sahidin, Didin; Herthira, Roro Tri Nur; Mekarsasi, Rindang; Maryamah, Rima; Fitriani, Rianti; Nugraha, Nanan; Marleni, Marleni (Indonesian Journal of Community Empowerment (IJCE), 2024)
language teachers’ competence in developing differentiated learning materials to improve students’ speaking skills. The descriptive method was applied, including training, mentoring, and workshops on creating learning materials tailored to students’ characteristics. The results indicate that teachers can design more varied materials, adjust difficulty levels according to individual needs, and enhance the effectiveness of speaking lessons. The implementation of differentiated learning materials also encourages active student participation, strengthens their confidence in speaking, and improves communication skills. This activity highlights the importance of responsive teaching strategies that accommodate diverse student abilities to achieve optimal learning outcomes